Impact of Mesenchymal Stromal Cells and Their Extracellular Vesicles in a Rat Model of Kidney Rejection - Ramirez-Bajo, Maria Jose; Rovira, Jordi; Lazo-Rodriguez, Marta; Banon-Maneus, Elisenda; Tubita, Valeria; Moya-Rull, Daniel; Hierro-Garcia, Natalia; Ventura-Aguiar, Pedro; Oppenheimer, Federico; Campistol, Josep M.; Diekmann, Fritz (Frontiers in Cell and Developmental Biology, 2020)
Background. Mesenchymal stromal cells (MSCs) from different sources possess great therapeutic potential due to their immunomodulatory properties associated with allograft tolerance. However, a crucial role in this activity resides in extracellular vesicles (EVs) and signaling molecules secreted by cells. This study aimed to evaluate the immunomodulatory properties of donor and recipient MSCs isolated from adipose tissue (AD) or bone marrow (BM) and their EVs on kidney outcome in a rat kidney transplant model. Methods. The heterotopic-kidney-transplant Fisher-to-Lewis rat model (F-L) was performed to study mixed cellular and humoral rejection. After kidney transplantation, Lewis recipients were assigned to 10 groups; two control groups; four groups received autologous MSCs (either AD- or BM- MSC) or EVs (derived from both cell types); and four groups received donor-derived MSCs or EVs. AD and BM-EVs were purified by ultracentrifugation. Autologous cell therapies were administered three times intravenously; immediately after kidney transplantation, 4 and 8 weeks, whereas donor-derived cell therapies were administered once intravenously immediately after transplantation. Survival and renal function were monitored. Twelve weeks after kidney transplantation grafts were harvested, infiltrating lymphocytes were analyzed by flow cytometry and histological lesions were characterized. Results. Autologous AD- and BM-MSCs, but not their EVs, prolonged graft and recipient survival in a rat model of kidney rejection. Autologous AD- and BM-MSCs significantly improved renal function during the first four weeks after transplantation. The amelioration of graft function could be associated with an improvement in tubular damage, as well as in T, and NK cell infiltration. On the other side, the application of donor-derived AD-MSC was harmful, and all rats died before the end of the protocol. AD-EVs did not accelerate the rejection. Contrary to autologous MSCs results, the single dose of donor-derived BM-MSCs is not enough to ameliorate kidney graft damage. Conclusion. EVs treatments did not exert any benefit in our experimental settings. In the autologous setting, BM-MSCs prompted as a potentially promising therapy to improve kidney graft outcomes in rats with chronic mixed rejection. In the donor-derived setting, AD-MSC accelerated progression to end-stage kidney disease. Further experiments are required to adjust timing and dose for better long-term outcomes.